2015
DOI: 10.1007/s00264-015-2861-0
|View full text |Cite
|
Sign up to set email alerts
|

A randomized study of autologous conditioned plasma and steroid injections in the treatment of lateral epicondylitis

Abstract: Purpose Chronic tendinopathy of lateral epicondyle of the humerus, commonly known as Btennis elbow^is one of the most frequent tendinopathies caused by recurrent overload of the muscle origins. The aim of the study was to assess the effectiveness of treating lateral epicondylitis (LE) with autologous conditioned plasma (ACP) and betamethasone injections, and to compare these methods over the course of a one year follow-up. Methods Patients were randomly placed into one of into two groups: 53 were treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…At this stage, 87 studies that did not meet the inclusion criteria were excluded. Twenty eligible RCTs were included in our network meta‐analysis (Figure ). In 13 PRP trials, the PRP preparation contained a high concentration of leukocytes in three trials and was relatively pure with deleted leukocytes in 10 trials .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At this stage, 87 studies that did not meet the inclusion criteria were excluded. Twenty eligible RCTs were included in our network meta‐analysis (Figure ). In 13 PRP trials, the PRP preparation contained a high concentration of leukocytes in three trials and was relatively pure with deleted leukocytes in 10 trials .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty eligible RCTs were included in our network meta‐analysis (Figure ). In 13 PRP trials, the PRP preparation contained a high concentration of leukocytes in three trials and was relatively pure with deleted leukocytes in 10 trials . Most studies measured outcomes at more than 2 months; only five studies measured outcomes at 3 weeks to 2 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] The most common reasons for exclusion were review paper (53), non-tendinopathy (14), injection of active control (7; eg, whole blood, PRP) and non-randomised study (7). Several manuscripts were excluded from this review because they were superseded by papers from the same study with longer follow-up including de Vos et al 29 30 and Peerbooms et al 31 A flow diagram of study identification and selection is shown in figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
“…Lateral epicondylitis (tennis elbow) is among the most frequent tendinopathies [1], as well as the most commonly diagnosed condition of the elbow [2]. It is prevalent as both a work-related disorder in strenuous jobs [3], and as a frequent overstrain injury in sports [4].…”
Section: Introductionmentioning
confidence: 99%